Migrasi Orang Banjar Ke Kabupaten Indragiri Hilir (Studi Etno-Sosiologi Tentang Peranan Modal Sosial Dan Jaringan Sosial Orang Banjar) - Edi Susrianto Indra Putra (Jurnal Edukasi, 2022)
The Banjar people who are in Indragiri Hilir district are one of the examples of ethnic groups that have good social capital and social networks. Their success in adapting and interacting with the various ethnic groups that exist makes them successful in the expedition. The success of the Banjar people in Indragiri Hilir is not only supported by a good work ethic but also because of their success in building social networks between their fellow ethnicities as well as with the various existing ethnic groups. This research will examine the role of social capital and social networks owned by Banjar people in the formation of interethnic relations that exist in Indragiri Hilir district. Banjar people in the concept of this research are people or ethnic descendants of Banjar who originated from South Kalimantan and now have long lived and settled in Indragiri Hilir district. The migration of Banjar people to Indragiri Hilir has been going on for decades. Their arrival in this region was not independent of the political and economic conditions that occurred in their area of origin at the time. Due to political and financial pressure in their region of origin, they migrated to various parts of Indonesia, in particular to Indragiri Hilir district. In order to maintain their existence in the destination area, they are required to adapt. With the social capital they have, they can adapt to the new area through the social network. Through a case study approach, it is expected to reveal various phenomena of migration, social capital, and social networks among Banjar people in Indragiri Hilir district.